Enterovirus A71 squamous epitheliotropism and infection in a hamster model and human organotypic and primary squamous cell culture system / Phyu Win Kyaw - Phyu, Win Kyaw (2017)
Enterovirus A71 (EV-A71) (Family: Picornaviridae, Genus: Enterovirus) is the one of most common and important causes of hand-foot-and-mouth disease (HFMD) in young children. Typical HFMD lesions in and around the oral cavity, palms, soles, and buttocks may be associated with severe neurological complications such as acute flaccid paralysis and acute encephalomyelitis. To study viral replication sites in the oral cavity, skin and other tissues, and to gain further insights into virus shedding, neuropathogenesis and person-to-person transmission, a novel, orally-infected, 2-week-old hamster model of HFMD and EV-A71 encephalomyelitis was developed. Hamsters developed the disease and died after 4-8 days post-infection (dpi); the LD50 was 25 CCID50. Macroscopic cutaneous lesions around the oral cavity and paws were observed. Squamous epithelium in the lip, oral cavity, paw, skin, and esophagus showed multiple small inflammatory foci and demonstrated viral antigens/RNA. Virus was isolated from oral washes, feces, brain, spinal cord, skeletal muscle, serum, and other tissues. To study viral spread and distribution, the hamster model was orally infected with 105 CCID50 viral dose and sacrificed at 1, 2, 3 and 4 dpi, respectively. Infected animals at 1 dpi remained healthy, all tissues were negative for viral antigens/RNA, and virus was not isolated, including in oral washes and feces. Although spinal cord was negative at 2 dpi, focal viral antigens in sensory ganglia and brainstem neurons were detected. The degree of infection in the CNS including spinal cord, gradually increased at 3 and 4 dpi, consistent with virus titration results. To model person-to-person transmission, animals (index cases) were orally-infected with 104 CCID50 virus dose. Index animals developed severe disease after 4-5 dpi, while iii littermates (contact cases) developed severe disease after 6-7 days post-exposure. Viruses in oral wash and feces were detected at 3-4 dpi in index animals and 3-8 days post-exposure in contact animals. Seroconversion in exposed, healthy mother hamsters was also detected. Based on the results, orally-shed virus was most likely from infected oral mucosa and salivary glands, while fecal virus could be from these sites as well as from oesophageal and gastric epithelia. The cellular target/s of EV-A71 in human skin and oral mucosa were investigated using human skin and mucosa organotypic cultures from the prepuce and lip, and primary prepuce squamous cells. Focal viral antigens/RNA were localized to cytoplasm of squamous keratinocytes or mucosal squamous cells in organotypic cultures as early as 2 dpi, and were associated with cytoplasmic vacuolation and cellular necrosis. Infected primary epidermal keratinocyte cultures showed cytopathic effects from 2 dpi, with concomitant detection of viral antigens/RNA in the cytoplasm corresponding to increasing viral titres over time. Thus, EV-A71 demonstrated squamous epitheliotropism in the prepuce and lip skin, and oral mucosa organotypic tissues. All other skin structures such as blood vessels, fibrous tissue, etc. showed no evidence viral infection. Neuroinvasion is likely via retrograde motor nerve transmission but intriguingly, our results show that sensory nerves may also play a role in neuroinvasion. In addition, the results from human organotypic and primary squamous cell culture systems strongly support EV-A71 squamous epitheliotropism both in the human skin and oral mucosa, and suggest that these organs are important primary or secondary viral replication sites that contribute significantly to viremia, oral and cutaneous viral shedding, and perhaps also cutaneous-oral transmission.